Contestation in Gamelan Making Rituals: Tensions between Old and New Understandings - Andri Handayani; Kelli Swazey (Humaniora, 2018)
Performing ritual before making gamelan as one of stages of producing gamelan orchestra has changed. The decision of gamelan masters to perform ritual is affected by their worldview, socio-religious and economic changes in their surroundings. This research aims to identify contestation in gamelan making rituals especially the tensions that occur between old and new understanding of gamelan masters. The study was conducted from March 2013 to April 2015. Semi-structured interview was applied to 6 out of 10 gamelan masters in Wirun Village, Sukoharjo District, Central Java. The result finds that gamelan masters apply strategies such as purification, negotiation and commercialization to adapt to the changes in Wirun. These strategies occur based on the understanding of old and younger generation of gamelan masters in Wirun. Purification can be defined as gamelan masters attempt to purify their religious principle from other external influence. There are two types of purification conducted by gamelan masters; purification of Javanese belief and purification of Islamic teachings. Negotiation hitherto is a way for gamelan masters to perceive their religious perspective and Javanese traditions flexibly. While, commercialization is taken by gamelan masters who only perceive gamelan as an industrial commodity and who prioritize the market value disregarding religious values in making the gamelan. The strategies serve to allow gamelan masters to sustain their identity as gamelan craftsmen.